Effect of supplementation of Turmeric, Black pepper and their combination as phytogenic feed additive on carcass characteristics and organoleptic parameters of Japanese quail: doi: 10.5958/2581-6616.2021.00003.7 - Kumar, V. D. Santhosh; Nath, Narendra; K, K. Naga Raja Kumari.; Kumar, D. Srinivas; T , T. Keerthana (Journal of Meat Science, 2022)
Day-old quail chicks (N=150) were distributed randomly into five treatments with three replicates containing ten birds  each and fed with five experimental diets T1 (Basal diet), T2 (Basal diet supplemented with 0.75% turmeric), T3 (Basal  diet supplemented with 1% black pepper), T4 (Basal diet supplemented with 0.25% turmeric and 0.5% black pepper)  and T5 (Basal diet supplemented with 0.5% turmeric and 1% black pepper). Carcass traits like mean dressing percentage,  weights of liver, heart, and gizzard did not show any significant difference among the treatment groups. The sensory  evaluation scores were improved significantly (p
Keywords: Black pepper; Carcass traits; Japanese Quail; Sensory evaluation; Turmeric